PENINGKATAN KETERAMPILAN MENULIS ARTIKEL ILMIAH UNTUK GURU BK MADRASAH ALIYAH PROVINSI BANTEN - Suryadi, Suryadi; Pahamzah, Prof. Dr. Jhon; Fachriyah, Eva (Bajang Institute, 2025)
Self-development, scientific publications, and innovative work are three methods used to achieve teacher skill development. The PKB program is designed to improve teacher skills gradually and continuously. Many teachers still struggle with the challenge of writing scientific papers. Most teachers experience difficulties in writing scientific papers. To overcome these obstacles faced by guidance and counseling teachers, this training was conducted to improve the writing skills of guidance and counseling teachers. This activity combines theoretical and practical approaches through interactive training aimed at improving teachers' understanding and writing skills. Evaluation results of PkM participants felt that it was very helpful in improving the writing competence of guidance and counseling teachers. Furthermore, survey results also provided information that almost all participants experienced an improvement in their scientific article writing skills. Through this training, teachers not only understood the concept of writing scientific articles theoretically, but were also able to apply it in practical applications. The positive impact of this training indicates that improving the scientific article writing skills of guidance and counseling teachers can be used as a reference in future guidance and counseling teacher writing competence improvement programs